2021
DOI: 10.1016/j.celrep.2021.110156
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of receptor binding domain mutations in SARS-CoV-2 variants of concern that modulate ACE2 and antibody binding

Abstract: The recently emerged SARS-CoV-2 Beta (B.1.351) and Gamma (P.1) variants of concern (VoCs) include a key mutation (N501Y) found in the Alpha (B.1.1.7) variant that enhances affinity of the spike protein for its receptor, ACE2. Additional mutations are found in these variants at residues 417 and 484 that appear to promote antibody evasion. In contrast, the Epsilon variants (B.1.427/429) lack the N501Y mutation, yet exhibit antibody evasion. We have engineered spike proteins to express these RBD VoC mutations eit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
86
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 66 publications
9
86
0
Order By: Relevance
“…3D). Additionally, the mutated residue Y501 in the Omicron RBD makes pi stacking interactions with Y41 in ACE2 as previously seen in the Alpha (B.1.1.7), Beta (B.1.351), and Gamma (P.1) variants (8,12), while mutated residue H505 is not hydrogen-bonded to E37 in ACE2 in contrast to what we reported previously for the Y505 residue (Fig. 3E) (20).…”
supporting
confidence: 64%
“…3D). Additionally, the mutated residue Y501 in the Omicron RBD makes pi stacking interactions with Y41 in ACE2 as previously seen in the Alpha (B.1.1.7), Beta (B.1.351), and Gamma (P.1) variants (8,12), while mutated residue H505 is not hydrogen-bonded to E37 in ACE2 in contrast to what we reported previously for the Y505 residue (Fig. 3E) (20).…”
supporting
confidence: 64%
“…5C ). Coincidentally, residues Y453, A475, Y489, R493, T500, Y501, and H505 of the Omicron RBD are important for ACE2 recognition and binding 14 . The neutralization activity test showed that 16L9 alone was able to broadly neutralize SARS-CoV-2 and SARS-CoV-2 variants.…”
Section: Resultsmentioning
confidence: 99%
“…For the 17 residues in RBD interfaces with Angiotensin-Converting Enzyme 2 (ACE2) 5 , eight were mutated in the different variants. In detail, K417N was observed in the Omicron, Beta and Gamma variants, which reduces ACE2 binding significantly 6,7 . Whereas N501Y, which exhibit increased ACE2 binding affinity 8,9 , was detected in all other 6 variants except Delta and Lambda.…”
mentioning
confidence: 95%